Նոր ընթերցումներ և մեկնաբանություններ Այանիսի նորահայտ ուրարտական սեպագրում - Հարությունյան, Նիկոլայ («Զանգակ - 97»)
The Tsolakert inscription of Menuas (KUKN, 48) and the Karmir blur inscription of Rusa II (KUKN, 424) shows that here the word iSerhini, probably, indicates on the time of some actions conducted by the Urartian kings; in the first case - after the conquest of Erikuahi, and the second - after Rusa՛ s accession. The Ayaiiis inscription also, like Karmir blur, teils about the crection of cultic objects after the accession of the king, and in the second case - the offering of vine for the gods during the sacrifices in the temple. In all cases the word iSerhini indicates the idea of the time.
Keywords: Հայոց պատմություն; Սեպագրություն